Redescriptions of two morphologically confusing sea lice Caligus aesopus Wilson, 1921 and C. spinosus Yamaguti, 1939 (Copepoda: Siphonostomatoida: Caligidae) parasitic on amberjacks (Seriola spp.) from Korea - Choe, Mi-Kyung; Kim, Il-Hoi (Zootaxa, 2010)
The taxonomically confusing species of sea lice Caligus aesopus Wilson, 1921 and C. spinosus Yamaguti, 1939 are redescribed based on material taken from gills of amberjacks (Seriola spp.) from Korean seas. These two sea lice can be distinguished from each other by the following major differences: (1) the female abdomen of C. aesopus has a lateral constriction in the distal third, but that of C. spinosus is fusiform, without a constriction; (2) the proximal process on the first antennal segment is subcircular distally in C. aesopus, but tapered in C. spinosus; (3) the basis of leg 1 has a small tubercle in C. aesopus, but none in C. spinosus; (4) the protopod (apron) of leg 3 of C. aesopus has an inner patch of less than 15 large spinules, but that of C. spinosus has a patch of more than 25 small spinules; (5) the innermost spine on the third exopodal segment of leg 4 is distinctly longer than the nearby middle spine in C. aesopus, but subequal to the middle spine in C. spinosus; (6) the inner margin of the first maxillipedal segment of the male has four processes in C. aesopus, but three in C. spinosus; and (7) the first maxillipedal segment of the female has a tubercle on the myxal area in C. aesopus, but absent in C. spinosus.